2021
DOI: 10.1016/j.redox.2020.101837
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterols present in Alzheimer's disease brain induce synaptotoxicity by activating astrocytes: A major role for lipocalin-2

Abstract: Among Alzheimer's disease (AD) brain hallmarks, the presence of reactive astrocytes was demonstrated to correlate with neuronal loss and cognitive deficits. Evidence indeed supports the role of reactive astrocytes as mediators of changes in neurons, including synapses. However, the complexity and the outcomes of astrocyte reactivity are far from being completely elucidated. Another key role in AD pathogenesis is played by alterations in brain cholesterol metabolism. Oxysterols (cholesterol oxidation products) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 89 publications
4
35
0
Order By: Relevance
“…In line, exogenous cholesterol addition in rat astrocytes triggered astrocyte activation, indicated by upregulation of glial fibrillary acidic protein (GFAP) ( Avila-Muñoz and Arias, 2015 ). Finally, exogenous addition of a mixture of oxysterols, representing oxysterols that are produced when cholesterol accumulates in the AD brain, promote upregulation of reactive astrocyte markers, which contributed to synaptotoxicity ( Staurenghi et al, 2021 ). In microglia, high cholesterol can affect immune function, as particularly studied in respect of cholesterol-rich myelin debris, which promotes inflammatory activation of microglia ( Cantuti-Castelvetri et al, 2018 ).…”
Section: Cholesterol As a Driver Of (Micro)glial Dysfunction And Gliosismentioning
confidence: 99%
“…In line, exogenous cholesterol addition in rat astrocytes triggered astrocyte activation, indicated by upregulation of glial fibrillary acidic protein (GFAP) ( Avila-Muñoz and Arias, 2015 ). Finally, exogenous addition of a mixture of oxysterols, representing oxysterols that are produced when cholesterol accumulates in the AD brain, promote upregulation of reactive astrocyte markers, which contributed to synaptotoxicity ( Staurenghi et al, 2021 ). In microglia, high cholesterol can affect immune function, as particularly studied in respect of cholesterol-rich myelin debris, which promotes inflammatory activation of microglia ( Cantuti-Castelvetri et al, 2018 ).…”
Section: Cholesterol As a Driver Of (Micro)glial Dysfunction And Gliosismentioning
confidence: 99%
“…This change was accompanied by the up-regulation of some reactive astrocyte markers and the release of pro-inflammatory molecules. Moreover, oxysterol-treated astrocytes have been shown to exert a synaptotoxic effect on mouse primary neurons, mainly mediated by lipocalin 2 release [ 104 ].…”
Section: The Role Of 24-ohc In Alzheimer’s Diseasementioning
confidence: 99%
“…This protein is involved in several processes including inflammation, iron metabolism, cell death, and cell survival, modulating the cellular response to Aβ [ 275 ]. Staurenghi et al demonstrated that increased levels of oxysterols observed in mild or severe AD brains, accompanied by increased levels of Lcn2, determine a clear morphological change in mouse primary astrocytes [ 276 ]. A recent study found that the iron chelators deferoxamine and deferiprone reduce Aβ-induced iron accumulation in astrocytes and inhibit Aβ-induced Lcn2, suggesting these molecules as promising therapeutic strategies against AD [ 205 ].…”
Section: Astrocytes As Targets For Ad Therapeuticsmentioning
confidence: 99%